Operative Techniques for Safe Scalp Dissection in Cranioplasty: Addressing Surgical Challenges - Mishra, Vineet Kumar; Kaif, Mohammad; Yadav, Kuldeep; Singh, Deepak Kumar; Kumar, Krishan; Sangolli, Praveen Kumar; Dabbir, Virinchi Kumar (Indian Journal of Neurotrauma, 2025)
Cranioplasty, a vital procedure in reconstructive neurosurgery, has undergone significant evolution with advances in surgical technique and biomaterials. The pseudolayer dissection approach (PDA) represents an innovative technique that enhances surgical precision, reduces soft tissue trauma, and improves patient outcomes. This article reviews the principles, technical nuances, advantages, limitations, and clinical outcomes associated with PDA in cranioplasty, establishing it as a promising method for achieving optimal functional and aesthetic reconstruction.
Keywords: biomaterials; cranioplasty; pseudolayer dissection approach